1965
DOI: 10.1042/bj0940536
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′-Triphosphate-Arginine Phosphotransferase From Lobster Muscle: Purification and Properties

Abstract: 1. A simple chromatographic method is described for the purification of arginine kinase from lobster (Homarus vulgaris) muscle. 2. Some physical properties and the effects on enzyme activity of ionic strength, pH, buffer salts, metal ions and substrates are reported. 3. The kinetic parameters, evaluated by variation of the concentration of one of the substrates, are dependent on the concentration of the other substrate. 4. The properties of the enzyme are discussed in relation to previous findings about phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

1971
1971
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 13 publications
(8 reference statements)
3
50
1
Order By: Relevance
“…The nature of the starting material probably accounts for the comparatively low specific activity of arginine kinase in the crude extract of whole flies. This activity is up to 10 times lower than in other reported purification procedures of arthropod arginine kinase where muscle tissue alone instead of whole animals could be used [6,22,23]. A typical purification protocol is summarized in Table 2.…”
Section: Purification and Characterizationmentioning
confidence: 80%
See 1 more Smart Citation
“…The nature of the starting material probably accounts for the comparatively low specific activity of arginine kinase in the crude extract of whole flies. This activity is up to 10 times lower than in other reported purification procedures of arthropod arginine kinase where muscle tissue alone instead of whole animals could be used [6,22,23]. A typical purification protocol is summarized in Table 2.…”
Section: Purification and Characterizationmentioning
confidence: 80%
“…This may have been caused by the high sensitivity of the enzyme towards oxidation. Since this behaviour is quite different from what is known of most of the other arthropod arginine kinases [6,22,23] we tested the stability of the enzyme by dialyzing it for 12 h in the presence and absence of sulfhydryl reagents a t different pH values ( Table 3). I n the presence of the sulfhydryl reagent the enzyme was stable a t pH values above 8.0.…”
Section: Purification and Characterizationmentioning
confidence: 99%
“…21 enzymes. Contradictory results were first reported : from kinetic experiments it was indicated that the reaction catalyzed by sea-crayfish arginine kinase occurred with the formation of a phosphorylated intermediate, via a "ping-pong" mechanism [5], while it was demonstrated with lobster arginine kinase that the reaction proceeded via a ternary complex between the nucleotidic substrate, the enzyme and the guanidine substrate [4].…”
Section: Mechanism Of the Reactionmentioning
confidence: 99%
“…However, additional difficulties were encountered owing to the small quantity of material available, its poor enzyme content, the numerous steps required for the purification, the low yield of the preparation and the instability of the enzyme even in the presence of protecting agents. In that respect, the enzyme differs greatly from the stable arginine kinase of Homarus vulgaris [3,4] and Palinurus longipes [22] and rather resembles the labile one from Sipunculus nudus [7]. …”
Section: Preparationmentioning
confidence: 99%
“…Arginine kinase from lobster, Homarus vulgaris, was prepared as described by Virden et al (1965). The enzyme from sea cucumber, Holothuriaforskali, was purified as described by Anosike et al (1975).…”
Section: Enzymesmentioning
confidence: 99%